PENGARUH INFLASI DAN SUKU BUNGA (BI) TERHADAP RETURN SAHAM PADA BANK BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Alya Putri Widianti (Laboratorium FEBI UIN SGD Bandung, 2024)
There is no single country whose economic growth is independent of the role of investment, one of the investment climate of a country is influenced by macroeconomic conditions such as inflation and interest rates. This study aims to examine and determine the effect of inflation and interest rate variables on stock returns at state-owned banks listed on the Indonesia Stock Exchange for the 2017-2021 period. The method used in this study is a descriptive and verifiative statistical analysis method with a quantitative approach. The data used for this study is secondary data obtained from the results of the company's financial statements that have been published through the official website. Furthermore, the data obtained were tested and analyzed using the eviews12 statistical analysis tool using the panel data regression analysis method through several stages. The results of this study show that inflation and interest rate variables have no effect on stock returns at state-owned banks listed on the Indonesia Stock Exchange during the 2017-2021 period. This shows that inflation and interest rates cannot be used as a reference for investors to invest. Investors need to pay attention to and analyze other factors than inflation and interest rates that have the potential to affect stock returns.